2018
DOI: 10.1038/s41598-018-34969-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of heterotrophic and autotrophic respiration to nitrogen addition and precipitation changes in a Tibetan alpine steppe

Abstract: Soil respiration (Rs) is an important source of atmospheric CO2 flux and is sensitive to changes in soil nutrient and water contents. Despite extensive studies on the effects of enhanced atmospheric nitrogen (N) deposition and changes in precipitation (P) on Rs, few studies have taken into account the effects of interactions between these factors on Rs of alpine grasslands. To address these questions, we investigated the effects of N addition (10 g N m−2 yr−1), changes in precipitation (±50% precipitation), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 77 publications
(88 reference statements)
2
16
1
1
Order By: Relevance
“…Aboveground biomass was sampled in mid‐August annually by clipping all plants within three 0.25 m × 0.25 m quadrates that were randomly placed within each plot and not overlapped spatially among years. Briefly, shoots were cut at the soil surface and oven‐dried at 65°C for 72 hr before they were weighed (Li et al, ). Thereafter, to assess the effect of altered precipitation, N addition, and their interaction on over all belowground biomass and aboveground biomass at different soil layer, we collected belowground biomass using three 8‐cm‐diameter soil cores from each plot in mid‐August 2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aboveground biomass was sampled in mid‐August annually by clipping all plants within three 0.25 m × 0.25 m quadrates that were randomly placed within each plot and not overlapped spatially among years. Briefly, shoots were cut at the soil surface and oven‐dried at 65°C for 72 hr before they were weighed (Li et al, ). Thereafter, to assess the effect of altered precipitation, N addition, and their interaction on over all belowground biomass and aboveground biomass at different soil layer, we collected belowground biomass using three 8‐cm‐diameter soil cores from each plot in mid‐August 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, shoots were cut at the soil surface and oven-dried at 65°C for 72 hr before they were weighed (Li et al, 2018). Thereafter, to assess the effect of altered precipitation, N addition, and their interaction on over all belowground biomass and aboveground biomass at different soil layer, we collected belowground biomass using three 8-cm-diameter soil cores from each plot in mid-August 2016.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different turnover times and controlling factors of plant and soil C pools (Wang, Sun, et al, ), R a and R h have showed differential responses to N enrichment (Fang et al, ; Li et al, ; Zeng, Zhang, & Wang, ). Multiple lines of evidence indicate that N application generally decreases R h when the added N exceeds microbial demand (Fang et al, ; Liu & Greaver, ; Peng, Li, et al, ), which has been explained by the decrease in soil microbial biomass (Treseder, ), inhibition of extracellular enzyme activities (Jian et al, ; Ramirez, Craine, & Fierer, ; Wang, Liu, & Bai, ), alterations in soil microbial abundance and composition (Zhang, Chen, & Ruan, ), and the increase in microbial C use efficiency (Finn et al, ; Liu, Qiao, Yang, Bai, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence indicate that N application generally decreases R h when the added N exceeds microbial demand (Fang et al, ; Liu & Greaver, ; Peng, Li, et al, ), which has been explained by the decrease in soil microbial biomass (Treseder, ), inhibition of extracellular enzyme activities (Jian et al, ; Ramirez, Craine, & Fierer, ; Wang, Liu, & Bai, ), alterations in soil microbial abundance and composition (Zhang, Chen, & Ruan, ), and the increase in microbial C use efficiency (Finn et al, ; Liu, Qiao, Yang, Bai, & Liu, ). The effect of N enrichment on R a is disparate, showing a positive (Fang et al, ; Li et al, ), neutral (Ren et al, ) or negative effect (Wei et al, ). A recent global synthesis revealed that N addition decreased R h by 8.1% and increased R a by 21.6%, resulting in no response of R s across all the terrestrial ecosystems (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%